2022
DOI: 10.3390/genes13122364
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Exome Sequencing and Copy Number Analysis in a Patient with Warburg Micro Syndrome

Abstract: Warburg Micro syndrome (WARBM) is an autosomal recessive neuro-ophthalmologic syndrome characterized by microcephaly, microphthalmia, congenital cataracts, cortical dysplasia, corpus callosum hypoplasia, spasticity, and hypogonadism. WARBM is divided into four subtypes according to the causative genes, of which RAB3GAP1 (OMIM# 602536) accounts for the highest proportion. We collected detailed medical records and performed whole-exome sequencing (WES) for a congenital cataract patient. A novel heterozygous fram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…More recently, Olfe et al have demonstrated CTLA-4 insufficiency due to a novel CTLA-4 deletion using ClinCNV ( German and Stephan, 2019 ; Olfe et al, 2023 ), further highlighting the synergy of CNV calling with WES analysis. Beyond the scope of autoimmune diseases, NGS techniques have also been extensively utilized in identifying causal variants (including CNVs) contributing to cancer ( van Dijk et al, 2014 ; Papp et al, 2021 ; Satam et al, 2023 ), congenital ( Lai et al, 2021 ; Li et al, 2022 ; Liu et al, 2022 ; Wang et al, 2022 ; Wu et al, 2022 ; Refeat et al, 2023 ), cardiovascular ( Hu et al, 2023 ) and hematological diseases ( Hassan et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Olfe et al have demonstrated CTLA-4 insufficiency due to a novel CTLA-4 deletion using ClinCNV ( German and Stephan, 2019 ; Olfe et al, 2023 ), further highlighting the synergy of CNV calling with WES analysis. Beyond the scope of autoimmune diseases, NGS techniques have also been extensively utilized in identifying causal variants (including CNVs) contributing to cancer ( van Dijk et al, 2014 ; Papp et al, 2021 ; Satam et al, 2023 ), congenital ( Lai et al, 2021 ; Li et al, 2022 ; Liu et al, 2022 ; Wang et al, 2022 ; Wu et al, 2022 ; Refeat et al, 2023 ), cardiovascular ( Hu et al, 2023 ) and hematological diseases ( Hassan et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%